An advanced incremental conductance MPPT technique considering time-varying solar irradiances. (August 2019) - Zhang, Lijun; Yu, Samson Shenglong; Chau, Tat Kei; Fernando, Tyrone; Iu, Herbert Ho-Ching
Abstract: For most of Maximum Power Point (MPP) Tracking (MPPT) techniques, their design principle are based only on output characteristics of photovoltaic (PV) panel under steady state, i.e., under constant solar irradiance. Because this steady state output characteristics do not describe how the operating point moves between different I-V curves under dynamic state, i.e., under varying solar irradiance, it inevitably results in poor dynamic performances or wrong perturbations. Focusing on this issue, in this paper, we propose the concepts of output characteristics of PV system which consist of two parts: output characteristics of PV system under steady state and output characteristics of PV system under dynamic state. Building on the output characteristics of PV system under two states, the widely used Incremental Conductance (Inc.Cond) technique is modified. Through simulation studies and the conventional Inc.Cond technique, the proposed advanced Inc.Cond technique retains good performances under steady state; under dynamic operation states, the MPPT performances are significantly improved.